Virtual screening of approved drugs as potential SARS-CoV-2 main protease inhibitors. (October 2020) - Jiménez-Alberto, Alicia; Ribas-Aparicio, Rosa María; Aparicio-Ozores, Gerardo; Castelán-Vega, Juan A.
Graphical abstract: Highlights: The main protease of SARS-CoV-2 has a highly flexible active site. Drug repurposing is a treatment opportunity in the current COVID-19 pandemic. Nine drugs merit testing as inhibitors of the SARS-CoV-2 main protease. Abstract: The global emergency caused by COVID-19 makes the discovery of drugs capable of inhibiting SARS-CoV-2 a priority, to reduce the mortality and morbidity of this disease. Repurposing approved drugs can provide therapeutic alternatives that promise rapid and ample coverage because they have a documented safety record, as well as infrastructure for large-scale production. The main protease of SARS-CoV-2 (Mpro) is an excellent therapeutic target because it is critical for viral replication; however, Mpro has a highly flexible active site that must be considered when performing computer-assisted drug discovery. In this work, potential inhibitors of the main protease (Mpro) of SARS-Cov-2 were identified through a docking-assisted virtual screening procedure. A total of 4384 drugs, all approved for human use, were screened against three conformers of Mpro. The ligands were further studied through molecular dynamics simulations and binding free energy analysis. A total of nine currently approved molecules are proposed as potential inhibitors of SARS-CoV-2. These molecules can be further tested to speed the development of therapeutics against COVID-19.